Cocoa Bar Antioxidant Profile Enrichment with Underutilized Apples Varieties - Alessandra Francini; Carmen Fidalgo-Illesca; Andrea Raffaelli; Marco Romi; Claudio Cantini; Luca Sebastiani (MDPI AG, 2022)
The impact of dried apples (Malus × domestica Borkh.) addition on improving the antioxidant characteristics of dark chocolate was evaluated. The antioxidant activity was measured through DPPH scavenging activity and showed an increase in the cocoa bar with 'Nesta' dry apple (17.3% vs. 46.8%) in comparison to cocoa mass. The 15 polyphenols analyzed by UHPLC-ESI-MS/MS indicated great variability among the apple varieties. Quercetin was detected in the highest concentrations (ranged from 753.3 to 1915.5 µg g−1), while the lowest were for kaempferol 7-O-glucoside, measured only in 'Mora' and 'Nesta' cocoa bars (from 0.034 to 0.069 µg g−1, respectively). P-coumaric acid, trans-ferulic acid, and chlorogenic acid contribute largely to the antioxidant activity in cocoa bars. Principal component analysis shows that a cocoa bar with the addition of 'Nesta' dry apple differ from others due to its higher content of polyphenols (1614 ± 61.8 mg gallic acid equivalents per 100 g). In conclusion, data confirm that cocoa bars with dry apples might be considered as a polyphenol-enriched food.